Definição de corredores ecológicos em espaços agrícolas abandonados para o Pagamento de Serviços Ambientais - Esperança do Sul/RS. - Jean Carlo Gessi Caneppele; Roberto Verdum; Lucimar de Fátima dos Santos Vieira (Confins)
Esperança do Sul/RS has a land structure of little proprieties that were colonized, mainly by German descendants, generating intense deforestation e fragmenting the areas of Atlantic Woods, with the fragments located in steep areas and nearly to watercourses. As from the abandoned of rural space, farmed areas are abandoned, with a change in use and occupation of earth, where tillage and pastures become regeneration areas of woods, in close relationship with their remnants. The research central objective, searches to define the ecological corridors which are formed with the connection between abandoned areas and fragments of woods. Besides that, it proposes to conceive as an economic alternative to the rural farmers of the municipality the Payment of Environmental Services to abandoned areas that connect the fragments, as also those who accrete the fragments. The methodology consisted at identification of wood’s fragments, with the definition of the larger fragments, after that, were identified the abandoned areas who connected into that fragments or those who accreted to the larger fragments. It has been identified 113 connector areas and 183 aggregator areas, around circa 66% of abandoned areas. As from the connection of abandoned areas with larger fragments, was possible the definition of seven ecological corridors that possibly extend to beyond the municipality limits expanding the area of corridors.